Concurrent B Cell Acute Lymphoblastic Lymphoma/Leukemia and Monoclonal B Cell Lymphocytosis: A Case Report with Extensive Molecular Analysis - Maryam Mehdipour Dalivand; Parastou Tizro; Julie Partain; Anita Aggarwal; Jack Lichy; Francisco Mot Ara; Victor E. Nava (Case Reports in Hematology)
Although acute lymphoblastic leukemia (ALL) and monoclonal B cell lymphocytosis (MBL) are common neoplasia, a simultaneous presentation is very unusual. Here, we present two different B cell clones, MBL and B-ALL, cocirculating in a 78-year-old African American male. Detailed molecular characterization revealed an unusual MPL (T487I) point mutation and unmutated VH4-39. After nonstandard chemotherapy, the patient remains in morphologic remission. These findings may stimulate further research to clarify the pathogenesis of hematologic neoplasms.